Heavy Metal Concentration in Fish Species Clarias gariepinus (Catfish) and Oreochromis niloticus (Nile Tilapia) from Anambra River, Nigeria - E. B. Ogbuene, A. M. Oroke, C. T. Eze, E. Etuk, O. G. Aloh, F. E. Achoru, J. C. Ogbuka, O. J. Okolo, A. V. Ozorme, C. J. Ibekwe, C. A. Eze and S. Akatakpo (Nature Environment and Pollution Technology, 2024)
Studies have emphasized that the presence of heavy metals in freshwater fish represents a global public health issue. Nigeria, being a developing nation with less emphasis on the quality of seafood consumed by the residents, ranks this study very vital. The policy implication of this study is the advancement of a healthy population in contemporary Nigeria. Hence, this study assessed heavy metal concentration in two fish species, Clarias gariepinus (Catfish) and Oreochromis niloticus (Nile Tilapia), in the Anambra River. The sample included twenty fishes, of which eighteen were collected from the three sampling locations (the fish ports of Anambra River), namely Otu-nsugbe, Otuocha, and Ikemivite) while two control samples were collected from a pond about 200 m away from the river. The levels of heavy metals were determined using Varian AA 240 atomic absorption spectrophotometer (AAS). The results showed that the concentrations of heavy metals (cadmium and arsenic) in the sampled fishes from Anambra River exceeded the joint World Health Organization and Food and Agriculture Organization (FAO/WHO) standard for fish and fish product consumption, while the concentration of chromium, mercury, and lead are within the permissible limit. The study also showed the distribution of the heavy metals in the fish organ varies among fish species. Heavy metals occur higher in Clarias garepinus than in Oreochromis niloticus, while tissue preference for heavy metal accumulation is in the order of gill > liver > muscle. It was recorded from this study that the heavy metal concentration in the fish from the pond is generally higher than the fish from the river for some metals. The high level of heavy metals in the sampled fish was attributed to heavy metals contamination of the river as a result of various anthropogenic activities such as mining, burning of fossil fuel and emission from the exhaust of boats/vehicles, overuse of fertilizers and pesticides, discharge of effluent, sewage, and hospital waste. This study concluded that long-term consumption of fish from the river may pose health risks to the consumers due to the possible bioaccumulation of heavy metals, especially cadmium and arsenic. It was recommended that continuous monitoring of heavy metal levels in the fish and water, public awareness, and appropriate legislative provisions should be put in place to ensure that harvested fish and fish products may be safe for human consumption.